2020
DOI: 10.1088/1757-899x/980/1/012077
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the effectiveness of chitosan and conventional coagulants for coal wastewater treatment

Abstract: In this research, the potential of chitosan to be used as a coagulant to treat coal wastewater was investigated, in comparison to a conventional coagulant, i.e: Al2(SO4)3 or aluminum sulfate, and Poly Aluminium Chloride (PAC). The parameters being studied were turbidity, pH, TDS, and TSS. The result of this research showed that chitosan worked as a more efficient coagulant to treat coal wastewater compared to alum and PAC, in terms of the needed dose of application. The optimum dose of chitosan was 20 mg/L tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
1
5
0
Order By: Relevance
“…Thus, a small amount of the dosage is already sufficient to destabilize particles. Similar results were also observed in the previous study [34][35][36], in which chitosan showed better effectiveness in a coagulation process at a lower dosage compared to the Al-based coagulants, with the additional advantages of being non-hazardous and more environmentally friendly [37,38].…”
Section: Response Surface Methodology (Rsm)supporting
confidence: 88%
“…Thus, a small amount of the dosage is already sufficient to destabilize particles. Similar results were also observed in the previous study [34][35][36], in which chitosan showed better effectiveness in a coagulation process at a lower dosage compared to the Al-based coagulants, with the additional advantages of being non-hazardous and more environmentally friendly [37,38].…”
Section: Response Surface Methodology (Rsm)supporting
confidence: 88%
“…These results indicated that the destabilization with chitosan is because of the presence of its amine groups that become protonated in an acid medium [43]. In this study, the protonation, where the carbohydrates increased was at pH 4.…”
Section: Optimization Of Harvesting Conditions (Fv Ft Settling Time A...mentioning
confidence: 46%
“…Chitosan from green scallop shells are also effective to remove COD, BOD, TSS levels in tofu industrial wastewater [25]. Coagulation by chitosan, alum, and PAC were all optimum within a range oh neutral pH [26]. Small dose of coagulant can inhibit coagulation process that is being lacking in floc cores, leaving more colloidal particles, so that the higher the dose of coagulant given, the colloidal particles combined to form more macrophages and leave fewer colloids in the final product [27].…”
Section: Discussionmentioning
confidence: 99%